PENGARUH TEKANAN KETAATAN DAN AUDIT INTERNAL TERHADAP PERILAKU KECURANGAN PELAPORAN KEUANGAN - Nafiati, Lulu (Universitas Ahmad Dahlan, 2018)
This study examines the effect of obedience pressure and internal audit function on fraudulent financial reporting behavior. Realities and previous studies have shown the strong effect of obedience pressure on fraudulent financial reporting behavior. However, few studies that examine mitigation strategies on that effect. This study proposes internal audit function to mitigate the effect of obedience pressure on fraudulent financial reporting behavior.This study uses experimental design 2x2 between subjects with students as surrogate. Hypothesis were tested by using ANOVA test. The results of study show that obedience pressure effect fraudulent financial reporting behavior and the effect is not able to be mitigated by using internal audit.